QSAR predictions on antichagas fenarimols - Duchowicz, Pablo Román (2022)
A useful QSAR model was developed to predict the antichagas activity for 760 fenarimol analogues obtained from the ChEMBL database, which are considered as very active and selective inhibitors of Trypanosoma cruzi. Various molecular descriptor programs provided a large number of 67,116 non-conformational molecular descriptors that were analyzed through multivariable linear regressions and the Replacement Method technique. Through THESE descriptors, the quantification of the structure–activity relationship achieves an acceptable statistical quality for compounds having experimental activity. The present work provides a prospective guide for predicting the inhibitory activity against T. cruzi of structurally-related fenarimol compounds.